The influence of three e-cigarette models on indoor fine and ultrafine particulate matter concentrations under real-world conditions. (December 2018) - Volesky, Karena D.; Maki, Anthony; Scherf, Christopher; Watson, Louis; Van Ryswyk, Keith; Fraser, Bruce; Weichenthal, Scott A.; Cassol, Edana; Villeneuve, Paul J.
Abstract: Electronic cigarette (e-cigarette) use has steadily increased since 2010. Indoor e-cigarette use exposes bystanders to a new source of particulate matter (PM) air pollution. Elevated short-term exposures to PM with a lower measuremented aerodynamic diameter (≤2.5 μm), PM2.5 and ultrafine particles (UFPs) have been linked to increased risk of adverse respiratory and cardiac events. This exposure study estimated concentrations of PM2.5 and UFPs from indoor e-cigarette use at 0.5 meters (m) and 1 m away from an e-cigarette user and investigated whether these indoor concentrations varied across three common e-cigarette models. One e-cigarette user tested three different e-cigarettes containing the same nicotine solution on three separate occasions and measured concentrations on PM2.5 and UFPs at 0.5 and 1 m in a ∼38 m 3 office. Continuous measures of PM2.5 and UFPs were taken for 5.5 min before e-cigarette use, then the user puffed seven times for 6.5 min (exposure), and for 10 min after ceasing e-cigarette use. Following the initiation of e-cigarette use, levels of PM2.5 increased 160-fold at a distance of 0.5 m, and 103-fold at 1 m. The corresponding increases in UFP counts were 5.2, and 3.0-fold higher, respectively. The PM2.5 concentrations and UFP counts between e-cigarette models were statistically significantly different at 1 m, but not at 0.5 m. There was substantial variability between distances, e-cigarettes, and replicates. This study indicates that e-cigarette vapors influence PM2.5 and UFPs concentrations/counts at close proximity distances indoors; additional research is needed to characterize the composition of those particles and evaluate the impacts of other e-cigarette solutions on indoor air quality. Graphical abstract: Image 1 Highlights: The mean PM2.5 concentrations increased by 160- and 103-fold at 0.5 and 1 m from an e-cigarette. The mean UFP counts increased by 5.2 fold at 0.5 m, and 3.0 fold at 1 m from an e-cigarette. There were significant differences in PM2.5 and UFP outputs between e-cigarettes at 1 m away from an e-cigarette user. Abstract : Fine particle pollution concentrations at 0.5 and 1 m away from one e-cigarette user were substantially higher than baseline concentrations and demonstrated distinguishable peaks in concentrations following the exhalation of e-cigarette vapors.